Nurses' knowledge, practice, and associated factors of pain assessment in critically ill adult patients at public hospitals, Addis Ababa, Ethiopia - Temesgen Ayenew; Berhanu Melaku; Mihretie Gedfew; Haile Amha; Keralem Anteneh Bishaw (Elsevier, 2021)
Background: As a result of the disease process and treatment effects, patients hospitalized to intensive care units typically feel undetected and untreated pain. Although it is crucial to assess pain in critically sick adult patients in order to manage it effectively, little research has been done on nurses' pain assessment knowledge and practice. Objective: To assess nurses' knowledge, practice, and associated factors of pain assessment in critically ill adult patients at public hospitals, Addis Ababa, Ethiopia. Methods: A cross-sectional study of 111 nurses was conducted, and variables with a p-value of 0.05 were considered statistically significant using binary logistic regression. Results: Sixty percent of nurses had adequate knowledge, whereas 55.9% had good practice. Workload [OR = 7.766, CI = 2.450, 24.617), sedation [OR = 7.628, CI = (2.348, 24.778)], and knowledge [OR = 5.219, CI = (1.673, 16.280)] were all associated to pain assessment practice. Conclusion: According to the study's findings, nearly half of the participants held adequate knowledge and practice. As a result, nurses' knowledge and practice should be expanded.